Beyond the hype: Exploring the Effectiveness of TikTok for Pre-service English Teachers' Speaking Development - Siti Nurjanah; Hamid, Ade Ismail Ramadhan (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
This study aims to investigate the utilization of TikTok to enhance the speaking ability and motivation of pre-service teachers at Muhammadiyah University of Kalimantan Timur. The primary focus is on exploring how incorporating TikTok into teaching practices can positively impact the development of speaking skills and motivation among pre-service teachers. The research methodology involves a mixed-method approach, combining surveys, interviews, and classroom observations. Initial findings suggest that integrating TikTok in teaching activities has the potential to engage students, boost motivation, and improve their speaking proficiency. These results have significant implications for the integration of technology in language education and can inform future strategies aimed at enhancing teaching and learning outcomes.